New constitutional horizons towards a pluralist constitutional theory - Mac Amhlaigh, Cormac (Oxford, United Kingdom ; Oxford University Press, 2022)
"We live in a pluralist world of transnational law and governance. More than ever before, multiple legal systems and governing authorities at different levels - state, supranational, international - are recognized as applying to, and claiming authority over, the affairs of the same sets of individuals and institutions. Yet our constitutional theories in terms of our conceptual toolkit of law and legitimate authority fail to adequately capture this pluralist state of affairs. This book examines some of the key conceptual and theoretical puzzles which the contemporary state of transnational pluralism poses for our constitutional theories. It offers fresh perspectives on these questions by addressing the pluralism of norms and authorities from the viewpoint of legality and legitimacy respectively, proposing novel solutions to how constitutional theory can be pluralized in the light of these perspectives. Our turbulent times are on a steady trajectory of ever-more pluralism of transnational law and governance to tackle the defining social and political problems of our age involving populism, pandemic and climate change and this book provides an essential intervention in debates on how to pluralize constitutional theory to better understand and, perhaps more importantly, legitimize the tools to address these shared global problems"--
The Circumstances of Constitutional Pluralism -- Part I: Legality -- 2. The Possibility of Constitutional Plurality -- 3. Law Beyond the Shadow of the State -- 4. Moving Beyond the Monist Manner in Theorizing Constitutional Plurality -- Part II: Legitimacy -- 5. Constitutional Dualisms -- 6. What's Wrong with Constitutionalism? Between Cacophony and Coercion -- 7. What's Wrong with Transnational Constitutionalism? Dealing with the No Demos Thesis -- 8. What's Right with (Transnational) Constitutionalism? Towards an Interpretive Transnational Constitutional Pluralism.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Access type: Perpetual access
Includes bibliographical references and index.
SOL
Mode of access: Internet
Keywords: Constitutional law; Legal polycentricity; International and municipal law; International law; Global legal pluralism, constitutional pluralism -- legality, legitimacy; Electronic books